“Soft” TQM and Performance of Local Government (A Case Study of Municipality of Tirana, Albania) - Rezarta Hasanaj; Mimoza Manxhari; Edmira Ozuni; Zamira Sinaj (European Scientific Journal, ESJ, 2021)
Nowadays, the philosophy of organizational management with the client at the center of managerial policies and operations, has been mastered not only by profitable organizations but also non-profit ones. Central and local government bodies, mainly in developed countries, have successfully applied consumer-oriented management philosophy. Quality management is one of the disciplines, equipped with all the theoretical and practical arsenal for the successful implementation of this orientation. It is being used as a productive and innovative tool, to achieve the objectives of profit and non-profit organizations. Providing quality services by local units means increasing the satisfaction of service beneficiaries (individual or organization), creating trust through transparent processes, accountability and democratic dialogue. The aim of this study is to assess the level of implementation of "soft" elements of Total Quality Management [TQM] according to the perception of employees in local units in the city of Tirana and its impact on performance.